Metode Perhitungan Angka Indeks Produktivitas Menggunakan Model Marvin E Mundel - Sarjono, Haryadi (Journal the Winners: Economics, Business, Management, and Information System Journal, 2001)
There are several measures and methods to basically perform the productivity of calculation. Marvin E Mundel (1978) methods uses calculation approachÂ  index number, which is amount that shows the difference change of time between basic period and actual period. The result can be decrease, stabil, or increase.